Susceptibility of agricultural pests of regional importance in South America to a Bacillus thuringiensis Cry1Ia protein - Berretta, Marcelo Facundo; Pedarros, Analía Soledad; Sauka, Diego Hernan; Perez, Melisa Paula; Onco, Maria Ines; Benintende, Graciela Beatriz (Elsevier, 2020)
Bacillus thuringiensis toxins of the Cry1I class have dual specificity for insects in the orders Coleoptera and Lepidoptera. We assessed the toxicity of a Cry1Ia protein from an Argentinian B. thuringiensis strain against agricultural pests in the families Tenebrionidae, Curculionidae, Noctuidae and Tortricidae. Three recombinant protein variants were produced that differed in length and fusion tag position to rule out artifactual results. The protein was toxic to Cydia pomonella and Rachiplusia nu. In contrast, Alphitobius diaperinus, Anthonomus grandis and Spodoptera frugiperda were not susceptible. The results are discussed with respect to previous studies and the prospective use of Cry1Ia in strategies to control major cotton pests in the region.